2016
DOI: 10.3201/eid2207.160168
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis E Virus Infection in Dromedaries, North and East Africa, United Arab Emirates, and Pakistan, 1983–2015

Abstract: A new hepatitis E virus (HEV-7) was recently found in dromedaries and 1 human from the United Arab Emirates. We screened 2,438 dromedary samples from Pakistan, the United Arab Emirates, and 4 African countries. HEV-7 is long established, diversified and geographically widespread. Dromedaries may constitute a neglected source of zoonotic HEV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 14 publications
7
60
0
Order By: Relevance
“…Bactrian camels and dromedary camels both belong to genus Camelus, but it seems that they are different as being hosts of many pathogens, such as Middle East respiratory syndrome (MERS) coronavirus (22) and West Nile virus (23). In all previous molecular surveillance studies on HEV in dromedary and Bactrian camels, as well as the present study, only HEV7 was found in dromedary camels and only HEV8 was detected in Bactrian camels (16,17,19), suggesting that dromedary and Bactrian camels are probably the sole natural hosts of HEV7 and HEV8, respectively. The separation of HEV genotypes may result from the species barrier and/or the geographical isolation of these two camel species.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Bactrian camels and dromedary camels both belong to genus Camelus, but it seems that they are different as being hosts of many pathogens, such as Middle East respiratory syndrome (MERS) coronavirus (22) and West Nile virus (23). In all previous molecular surveillance studies on HEV in dromedary and Bactrian camels, as well as the present study, only HEV7 was found in dromedary camels and only HEV8 was detected in Bactrian camels (16,17,19), suggesting that dromedary and Bactrian camels are probably the sole natural hosts of HEV7 and HEV8, respectively. The separation of HEV genotypes may result from the species barrier and/or the geographical isolation of these two camel species.…”
Section: Discussionsupporting
confidence: 43%
“…These four genotypes are the major genotypes that circulate in humans causing hepatitis E. HEV5 and HEV6 have been identified in wild boar in Japan, but the zoonotic risk of these two genotypes is still unknown (15). More recently, HEV7 has been isolated from dromedary camels in Dubai, United Arab Emirates (16), and several other countries (17). A case report of chronic infection of a human by HEV7 has appeared, indicating that zoonotic transmission of this HEV genotype can occur (18).…”
mentioning
confidence: 99%
“…Besides HEV‐1 to HEV‐4, a new potentially human pathogenic HEV genotype (HEV‐7) has been described recently (Rasche et al., ; Woo et al., ). This genotype seems to be widely distributed in dromedary camels ( Camelus dromedarius ) from the Middle East (Rasche et al., ; Woo et al., ).…”
Section: Transmission Pathways To Humansmentioning
confidence: 99%
“…Four of nine publications on Camelpox discussed human transmission, including a paper that reported the first laboratory-confirmed case of human Camelpox (Bera et al 2011). There were five papers on hepatitis E, one of the five known human hepatitis virus strains, in which camel meat and milk were implicated as risk factors in humans through whole-genome sequencing, HEV IgM, or HEV RNA detection (Pavio et al 2015 Khuroo andKhuroo 2016;Lee et al 2016;Rasche et al 2016;Spahr et al 2018). In one of these reports, a liver transplant patient in the United Arab Emirates consumed camel meat and milk regularly and was chronically infected with hepatitis E (Lee et al 2016).…”
Section: Viralmentioning
confidence: 99%